Projekt ustawy o działalności franczyzowej - Adamus, Rafał (The Opole Studies in Administration and Law, 2024)
This study is a revised draft of the Franchise Act together with the justification, previously prepared for the Institute of Justice in Warsaw, in connection with the initiated work on regulating the issue of franchising in Poland. In 2023, a draft act on franchising activities, in some way referring to this study, was presented for legislative work. This project was published too late to be subjected to legislative procedures in the Sejm of the ninth term. Franchising, as a private law institution, has not yet been regulated in Polish law. The presented draft law may constitute a reference point for possible further legislative work.